Rhinovirus is associated with severe adult community-acquired pneumonia in China - Wang, Keqiang; Xi, Wen; Yang, Donghong; Zheng, Yali; Zhang, Yaqiong; Chen, Yusheng; Yan, Chunliang; Tian, Guizhen; An, Shuchang; Li, Xiangxin; An, Fucheng; Du, Juan; et al. (Journal of Thoracic Disease, 2017)
Background: Human rhinovirus (HRV) is one of the most common viral etiologies detected in community-acquired pneumonia (CAP) adult cases. However, few is known about the characteristics of HRV-associated CAP. To describe the clinical features of HRV-associated CAP in immunocompetent adults admitted to multiple medical centers in mainland China over a 2-year period. Methods: A total of 383 patients admitted to hospitals for CAP were enrolled from 46 medical centers in mainland China between January 2013 and December 2014. Multiplex real-time polymerase chain reaction (RT-PCR) assays for viral detection and DNA-based quantitative loop-mediated isothermal amplification (qLAMP) assays for bacterial detection were implemented to all lower respiratory tract specimens obtained from the patients. Twenty-eight cases (28/383, 7.3%) revealed HRV-positive PCR results. Patients with bronchoalveolar lavage (BAL) HRV-positive PCR results (n=20) were further enrolled and divided into two groups depending on the status of bacterial co-infection (viral group, n=12; viral-Bacterial group, n=8). Demographic, clinical and microbiological data were reviewed and compared in detail. Results: Cases with HRV-infection were remarkably correlated with respiratory failure (14/20) and most of them (13/14) received mechanical ventilation. Fever (17/20), productive cough (15/20) and dyspnea (6/20) were common symptoms while flu-like symptoms were rarely observed in the cohort. Streptococcus pneumoniae (3/8), Klebsiella pneumoniae (3/8) and Mycoplasma pneumoniae (2/8) were most frequently identified bacterium in the viral-bacterial group. Compared with the viral group, higher incidence of septic shock (3/8 vs. 1/12, P=0.255), longer ICU length of stay (LOS) (10.0 vs. 6.5 days, P=0.686), longer hospital LOS (18.5 vs. 13.0 days, P=0.208) and higher 28-day mortality (2/8 vs. 2/12, P=1) were observed in the Viral-Bacterial group, although without statistically significant difference. Conclusions: HRV is a common etiology in CAP among China adults, especially in severe CAP. Clinicians should be vigilant considering of the poor outcome. Highly qualified multiplex PCR techniques with invasive sampling are needed to increase the detection rate.